2018
DOI: 10.1021/acsami.7b17933
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Dipeptide Nanobelts Based on Solid–Solid Phase Transformation Self-Assembly and Their Polarization Imaging of Cells

Abstract: Controlled phase transformation involving biomolecular organization to generate dynamic biomimetic selfassembly systems and functional materials is currently an appealing topic of research on molecular materials. Herein, we achieve by ultrasonic irradiation the direct solid−solid transition of bioinspired dipeptide organization from triclinic structured aggregates to nanofibers and eventually to monoclinic nanobelts with strong polarized luminescence. It is suggested that the locally high temperature and press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(44 citation statements)
references
References 48 publications
(71 reference statements)
0
42
0
2
Order By: Relevance
“…In addition, the PCL/PEO fibers (Sample 1) prepared for different SVA treatment durations were characterized by XRD, which was important for self-assembled composite materials [68][69][70][71][72][73][74][75]. The XRD pattern of PCL (Fig.…”
Section: Structural Characterization Of the Air Filtration Matsmentioning
confidence: 99%
“…In addition, the PCL/PEO fibers (Sample 1) prepared for different SVA treatment durations were characterized by XRD, which was important for self-assembled composite materials [68][69][70][71][72][73][74][75]. The XRD pattern of PCL (Fig.…”
Section: Structural Characterization Of the Air Filtration Matsmentioning
confidence: 99%
“…Yan et al. have shown that similar crystalline nanobelts can be beneficial to precisely inspect the nanoscale delivery by using polarization imaging of cells without using labeled fluorescent dyes . As crystals were very thin and delicate, we were not able to perform single crystal diffraction experiments.…”
Section: Resultsmentioning
confidence: 94%
“…One-dimensional nanorods and nanowires are able to enhance electronic/ionic conductivity and shorten ion transport pathway for faradaic reactions. [20][21][22][23][24] In China, the resources of low grade manganese ore is very rich, and it is not exploited and utilized due to the low content of manganese and high cost. In this paper, MnO 2 nanowire was prepared successfully from the manganese dioxide by hydrothermal method.…”
Section: Introductionmentioning
confidence: 99%